Natural mode entanglement as a resource for quantum communication - Heaney, L; Vedral, V (2011)
Natural particle-number entanglement resides between spatial modes in coherent ultracold atomic gases. However, operations on the modes are restricted by a superselection rule that forbids coherent superpositions of different particle numbers. This would seemingly prevent mode entanglement from being used as a resource for quantum communication. Here I demonstrate that mode entanglement of a single massive particle can be used for dense coding despite the superselection rule if both parties share a coherent reservoir. © 2011 American Institute of Physics.